Evaluation of death records of Izmir Metropolitan Municipality Directorate of Cemeteries and Izmir Provincial Health Directorate in 2010: Consistency and completeness of notifications - Raziye Özdemir; Zeliha Öcek (Turkish Society of Public Health Specialists, 2015)
Abstract Objective: The aim of the study was to determine the consistency of death records of Izmir Metropolitan Municipality Directorate of Cemeteries and Izmir Provincial Health Directorate in 2010 and to provide a quantitative estimate of deaths that occurred in Izmir in 2010 through capture-recapture method. Methods: In this descriptive study, we examined whole death records of Izmir Provincial Health Directorate and Izmir Metropolitan Municipality Directorate of Cemeteries in 2010. The records of both institutions were matched exactly to evaluate the consistency of reporting. Missing records which were registered by only Directorate of Cemeteries, but not registered by Provincial Health Directorate were added the database of Provincial Health Directorate. The two source capture-recapture method implemented based on the records of two institutions. The number of deaths by age group and gender and level of completeness of Provincial Health Directorate records were calculated through this method. The observed and calculated numbers of death and summary mortality of measures of Provincial Health Directorate were compared with database of Turkish Statistical Institute (TURKSTAT). Results: 8.9% of deaths which registered at the Directorate of Cemeteries were missing at Provincial Health Directorate. Missing notifications showed concentration in the younger age groups, mainly stillbirths (98.6%) and infant deaths (46.9%). Decedents' residence addresses of records which matched both instuitions were inconsistent. The level of completeness of Provincial Health Directorate records were 88.6% for male and 89.3% for female according to calculations using capture-recapture method. Calculated infant mortality rate and under five mortality rate were higher than the rates of observed records of Provincial Health Directorate and the TURKSAT data. Conclusions: This study indicates that the death records are insufficient in terms of reliability. Control mechanisms which provided in the system are required to be operated more efficiently to ensure coordination among the institutions and to execute complete and timely notifications. Key Words: Death statistics, burial records, consistency, completeness.